Pengembangan Media Video Tutorial Tari Lenggang Surabaya berbasis Digital sebagai Pembelajaran Tari di Sanggar - Virdha Annora Zavira; Setyo Yanuartuti (Jurnal Pendidikan Sendratasik, 2025)
The research was conducted because the teaching of Lenggang Surabaya dance in several studios is still facing challenges due to the lack of complete digital teaching media, making it difficult for students to understand movement details, memorize sequences, and match movements with the music rhythm. This study aims to describe the development process, produce quality instructional video media, and find out its practicality in dance learning at studios. This research uses the ADDIE development method, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of pre-teen and teen students at the Brangwetan studio. Data collection was carried out through observation, interviews, questionnaires, and documentation. The study results showed that the instructional video developed received a very feasible validation score of 89.13% and was very practical with a score of 86.36%. Therefore, the Lenggang Surabaya dance instructional video is effective for supporting dance learning, enhancing students' creativity, and helping preserve local culture.